Analyzing Production Records of Commercial Sweet Orange Blocks to Measure Effects of Mechanical Harvesting on Long-Term Production and Tree Health - Fritz M. Roka; Lisa H. House; Katrina R. Mosley (EDIS, 2014)
Ever since mechanical harvesting systems were introduced in the 1960s, growers expressed serious concerns over the potential negative impact mechanical harvesting could have on their trees. A study was undertaken in 2010 to analyze grower production data and compare whether mechanical harvesting had an adverse effect on fruit yield or shortened tree longevity as compared to hand harvesting. The purpose of this article is to describe how the study was organized and to summarize its results and conclusions. This 4-page fact sheet was written by Fritz M. Roka, Lisa H. House, and Katrina R. Mosley, and published by the UF Department of Food and Resource Economics, May 2014.